Patterns of care for patients with advanced soft tissue sarcoma: experience from Australian sarcoma services. Issue 1 (December 2016) - Bae, Susie; Crowe, Philip; Gowda, Raghu; Joubert, Warren; Carey-Smith, Richard; Stalley, Paul; Desai, Jayesh
Abstract Background There is a paucity of data on the current management of patients with advanced soft tissue sarcoma (STS) in the Australian health care setting. This study utilised the Australian sarcoma database to evaluate the patterns of care delivered to patients with advanced STS at Australian sarcoma services. Methods Prospectively collected data from six sarcoma centres in Australia were sourced to identify patients diagnosed with advanced STS between 1 January 2010 and 31 December 2012. Descriptive statistics were analysed for patient demographics, clinicopathological characteristics and treatment patterns. Overall survival was estimated using the Kaplan–Meier product limit method. Results Of 253 patients with advanced STS, four major STS subtypes were identified: undifferentiated pleomorphic sarcoma (23 %), leiomyosarcoma (17 %), liposarcoma (14 %), and synovial sarcoma (8 %); with the rest grouped as "other STS" (38 %). Approximately one-third of patients received palliative systemic therapy with the most common first-line therapy being doxorubicin alone (50 %). A small percentage of patients participated in clinical trials (20 %). Palliative radiotherapy was utilised mostly for treatment of symptomatic distant metastases and one-third of patients underwent metastasectomy, most commonly for pulmonary metastases. The median overall survival (OS) in this series was 18 months and no significant difference in OS was observed across different STS histological subtypes. Conclusions This is the first detailed study outlining patterns of care for Australian patients with advanced STS managed at sarcoma services. These data highlight a particular area of weakness in the lack of clinical trials for sarcoma patients and also serve as an important reference point for understanding how practice may change over time as treatment options evolve.